Jawabanmu

2014-06-07T19:13:53+07:00
27. jawaban'a b.-3

29.
  \left[\begin{array}{ccc}2x&1\\-3&7\\\end{array}\right] -  \left[\begin{array}{ccc}y&x\\x&6\\\end{array}\right] +  \left[\begin{array}{ccc}2&y\\y&x\\\end{array}\right] =  \left[\begin{array}{ccc}3&x\\-x&y\\\end{array}\right]
  \left[\begin{array}{ccc}2x-y&1-x\\-3-x&1\\\end{array}\right] +   \left[\begin{array}{ccc}2&y\\y&x\\\end{array}\right] =  \left[\begin{array}{ccc}3&x\\-x&y\\\end{array}\right]
  \left[\begin{array}{ccc}2x-y+2&1-x+y\\-3-x+y&1+x\\\end{array}\right] =  \left[\begin{array}{ccc}3&x\\-x&y\\\end{array}\right]
maka persamaan'a menjadi
2x-y+2=3
-3-x+y=-x
1-x+y=x
1+x=y
maka, kita ambil satu persamaan
-3-x+y=-x
-3+y   = -x+x
-3 + y = 0
y        = 3

1+ x = y
1 + x = 3
     x  = 3-1 = 2

maka x= 2, y = 3

jadi, x-xy+3y = 2- (2)(3) + 3(3) = 2- 6 + 9 = 5
jadi jwban'a d

30. 2 x^{2} +5x+3=0 \\ 
(2x+3) (x+1) \\ 
maka, \\ 
2x+3=0 \\ 
2x=-3 \\ 
x=-3/2 \\  \\ 
x+1=0 \\ 
x=-1

jadi jwabn'a b.